2013
DOI: 10.1016/j.ijsu.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The RML of lymph node metastasis was superior to the LODDS for evaluating the prognosis of gastric cancer

Abstract: RML staging was the best system for prediction the OS of the gastric cancer patients following radical gastrectomy plus extended lymphadenectomy, rather than LODDS staging, NLN staging or N staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…The number-based lymph node staging system of UICC classification (seventh edition) was widely used, although a principle flaw is that the prognostic accuracy is influenced by the number of total retrieved lymph nodes [8, 9]. The most recent NCCN guideline recommends that D2 lymphadenectomy should be used to remove an adequate number of lymph nodes (no less than 15); however, some studies reported that ≥15 lymph nodes are harvested in only 29 and 60.2 % of cases in the USA [10] and China [11]. Moreover, the optimal number of retrieved lymph nodes to avoid stage migration remains unclear in some studies [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…The number-based lymph node staging system of UICC classification (seventh edition) was widely used, although a principle flaw is that the prognostic accuracy is influenced by the number of total retrieved lymph nodes [8, 9]. The most recent NCCN guideline recommends that D2 lymphadenectomy should be used to remove an adequate number of lymph nodes (no less than 15); however, some studies reported that ≥15 lymph nodes are harvested in only 29 and 60.2 % of cases in the USA [10] and China [11]. Moreover, the optimal number of retrieved lymph nodes to avoid stage migration remains unclear in some studies [12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…20 Additionally, in the study of Sun et al, the LODDS staging system was shown to be superior to pN and LNR classifications, but this was restricted to patients in whom an insufficient number of LNs were retrieved. 18 Two other studies that compared LN staging systems did not demonstrate superiority of LODDS over LNR, 22,23 but in one of them, only patients with more than 15 LNs analyzed were included. 22 Some studies have previously reported that the LNR staging system can also be useful to discriminate prognosis among pN1 and pN2 patients even when fewer than 15 LNs are analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…18 Two other studies that compared LN staging systems did not demonstrate superiority of LODDS over LNR, 22,23 but in one of them, only patients with more than 15 LNs analyzed were included. 22 Some studies have previously reported that the LNR staging system can also be useful to discriminate prognosis among pN1 and pN2 patients even when fewer than 15 LNs are analyzed. 16,17 However, the LNR system can only differentiate prognoses between patients with positive LNs; moreover, the LNR seems not accurate enough in discriminating survival rates from patients in which all LNs are metastatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic significance of a number of clinical parameters has been examined for patients with GC subsequent to radical surgery (8)(9)(10)(11)(12)(13)(14)(15). Of these, the preoperative prognostic nutritional index (PNI) as a reflection of the immunological and nutritional condition of the patients has been associated with the outcomes of patients who undergo gastrectomy for a number of stages of GC (10,11,16,17).…”
Section: Introductionmentioning
confidence: 99%